An introduction to Jungian coaching - Goren-Bar, Avi (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Based on the psychology of Carl Jung, this illuminating new book invites coaches to extend their toolbox with deep, creative and efficient professional methods which derive from a new perspective on coaching. In using the unconscious archetypes as a practical active psychological database for change, the Jungian coach can contribute significant modification in the coachee's expected behaviour. Jungian Coaching can be applied in evaluating the coachee, the team and the corporation. This book translates Jungian psychology into simple comprehensive concepts. Each chapter offers theoretical concepts and rationale translated to the coaching practice and it illustrates practical examples from corporate world as well as from life coaching and it offers Jungian coaching tools and techniques. By overlapping the Gestalt psychology principle of the 'here and now' over Jungian concepts, the author develops a new coaching tool which enables an activation of archetypes as a coaching useful empowering experience. A valuable introductory resource for all those involved in coaching relationships, this book can empower coachees and serve as a compass for personal growth. It will be of great interest to practicing coaches, executives, human resource managers, consultants and psychotherapists"--
Keywords: Personal coaching; Jungian psychology; Counseling psychology; PSYCHOLOGY / Industrial & Organizational Psychology; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / Jungian